Genetic complexity of Plasmodium falciparum in two ethnic groups of Burkina Faso with marked differences in susceptibility to malaria. - Paganotti, G; Babiker, H; Modiano, D; Sirima, B; Verra, F; Konaté, A; Ouedraogo, A; Diarra, A; Mackinnon, M; Coluzzi, M; Walliker, D (2004)
We have characterized Plasmodium falciparum genotypes among the Mossi and Fulani sympatric ethnic groups in villages in Burkina Faso during the rainy season. Differences in clinical malaria presentation and in immune responses to malaria occur between the two groups. Asexual parasite rate, density, and gametocyte rate were higher among the Mossi than the Fulani. There was no difference in frequencies of alleles of the P. falciparum merozoite surface protein 1 (msp-1), msp-2, and glutamate-rich protein (glurp) genes among the parasites in each group. However, there were significant differences in the mean number of P. falciparum clones in the two populations, with there being more in the Mossi than in the Fulani. This effect was especially marked in older children. These differences can most probably be attributed to genetic differences in immune responsiveness to malaria between the two ethnic groups.